2012
DOI: 10.1007/s00259-012-2180-2
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of planar 123I-meta-iodobenzylguanidine (MIBG) myocardial scintigraphy in patients with heart failure

Abstract: PurposeDespite its high prognostic value, widespread clinical implementation of 123I-meta-iodobenzylguanidine (MIBG) myocardial scintigraphy is hampered by a lack of validation and standardization. The purpose of this study was to assess the reliability of planar 123I-MIBG myocardial scintigraphy in patients with heart failure (HF).MethodsPlanar myocardial MIBG images of 70 HF patients were analysed by two experienced and one inexperienced observer. The reproducibility of early and delayed heart-to-mediastinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 25 publications
(39 reference statements)
4
38
0
Order By: Relevance
“…This result is important for the future development of this radiotracer in subsequent clinical trials. Finally, the good reproducibility of planar measurements is concordant with a previous report of high reproducibility (22).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result is important for the future development of this radiotracer in subsequent clinical trials. Finally, the good reproducibility of planar measurements is concordant with a previous report of high reproducibility (22).…”
Section: Discussionsupporting
confidence: 80%
“…Verberne et al reported higher H/M ratios in 9 healthy volunteers using a no-carrier-added formulation (20); however, these higher H/M ratios could be attributed to acquisition on medium-energy collimators that reduce septal penetration and scatter of the higherenergy g photons from 123 I (21). As expected, all SPECT H/M ratios were higher than their respective planar values; however, the variability in normal SPECT H/M measurements was high, as previously reported (22). No significant difference in SPECT H/M ratios could be demonstrated when HSA MIBG and LSA MIBG were compared using this limited sample size.…”
Section: Discussionmentioning
confidence: 48%
“…A cardiac region of interest (ROI) is set manually over the heart without overlapping lung and liver activities and with a rectangular mediastinal ROI as a background (26). The reproducibility of the HMR is good within an institution (27), although variability can be observed, depending on the selection of the ROI size and location and the operator's experience. Recently, software (smartMIBG; Fujifilm RI Pharma Co., Ltd.) became available for semiautomatic ROI settings and calculations of the HMR and WR (28).…”
Section: Parameters Of 123 I-mibg Studiesmentioning
confidence: 99%
“…Veltman et al demonstrated high intra-observer and inter-observer reliability, even among both experienced and inexperienced technologists. 24 A subsequent study by Pellegrino et al also demonstrated high intra-observer and inter-observer reproducibility among experienced readers. 25 The study by Bateman et al in this volume of the Journal addresses the second factor.…”
mentioning
confidence: 99%